2022
DOI: 10.3390/ijerph19031702
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Veterinary Antibiotics in Farmland Soil: Effects of Dissolved Organic Matter

Abstract: The application of manure as a fertiliser to farmland is regarded as a major source of veterinary antibiotic (VA) contamination in the environment. The frequent detection of such emerging contaminants and their potential adverse impacts on the ecosystem and human health have provoked increasing concern for VA transport and fate. Extrinsic dissolved organic matter (DOM) may be introduced into farmland soil along with Vas, and thus exert significant effects on the transport of VAs via hydrological processes upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 148 publications
(258 reference statements)
0
13
0
Order By: Relevance
“…Many studies have also shown that the absorption of antibiotics into sediments is influenced by changes in the flow and volume of water and its physicochemical properties (e.g., water temperature and the pH of water and sediments) [ 69 ]. Based on previous studies, the mobility of antibiotics increases in the presence of dissolved organic carbon and colloidal matter [ 70 , 71 ]. Kafaei et al (2018), Zhao et al (2016), and Cheng et al (2016) have stated that the uptake of antibiotics by sediments is influenced by the pH and the contents of clay, silt, organic matter, and ionic matter of sediments [ 50 , 56 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have also shown that the absorption of antibiotics into sediments is influenced by changes in the flow and volume of water and its physicochemical properties (e.g., water temperature and the pH of water and sediments) [ 69 ]. Based on previous studies, the mobility of antibiotics increases in the presence of dissolved organic carbon and colloidal matter [ 70 , 71 ]. Kafaei et al (2018), Zhao et al (2016), and Cheng et al (2016) have stated that the uptake of antibiotics by sediments is influenced by the pH and the contents of clay, silt, organic matter, and ionic matter of sediments [ 50 , 56 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, antibiotics are the PhACs that generate a major concern because of their continuous consumption and discharge into the sewer system, biological activity against living organisms, and the increase of antibiotic-resistant bacteria [ 1 ]. The presence of antibiotics in agricultural soil, not only from sludge and wastewater reuse but also from animal manure, has been described in several papers [ 2 , 3 , 4 ]. For example, antibiotics, such as fluoroquinolones, sulfonamides, macrolides, or tetracyclines, were measured in agricultural soils at concentrations up to the mg per kilogram level [ 3 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites are produced by demethylation of the parent compound (3-desmethyl-trimethoprim (DM-TMP), 65% of metabolized TMP, and 4-desmethyl-trimethoprim, 25% of metabolized TMP), and by its hydroxylation (4-hydroxy-trimethoprim (OH-TMP), 2% of metabolized TMP) [ 9 ]. These compounds could not only affect the soil organism but also contaminate surface water through runoff, groundwater by leaching, or even crops entering the food chain [ 2 , 10 ]. However, to date, there are no studies focused on the distribution and presence of these metabolites in soil, even though they may possess the same biological activity as the parent compound, or they could be present at higher concentrations or even more toxic than their parent compound [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,24,49,50 Furthermore, hydrophobicity is one of the important functional properties of natural organic matter affecting its interactions with antibiotics. 51,52 Particularly, the hydrophobicity fraction of natural organic matter was found to play a critical role in controlling the fate of organic contaminants including antibiotics in the environment. 51,52 That is, HA coating has the potential to alter the physicochemical characteristics of sand grain surfaces ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 Particularly, the hydrophobicity fraction of natural organic matter was found to play a critical role in controlling the fate of organic contaminants including antibiotics in the environment. 51,52 That is, HA coating has the potential to alter the physicochemical characteristics of sand grain surfaces (e.g., enhanced the hydrophobicity of the sand surface). 28,53,54 Thus, hydrophobic interaction also contributed the interaction between OTC and HA molecules.…”
Section: Transport Of Otc Through Saturated Porous Media With Differe...mentioning
confidence: 99%